2010
DOI: 10.1002/acr.20261
|View full text |Cite
|
Sign up to set email alerts
|

Bone density consequences of initiation and compliance with therapy for osteoporosis

Abstract: Objective. There are many effective osteoporosis (OP) medications with a variety of dosing intervals and delivery options, but even when diagnosed, OP is often undertreated. We sought to determine the bone density consequences of the decision to initiate and comply with therapy for OP. Methods. We identified 243 women who received a dual x-ray absorptiometry (DXA) evaluation and fulfilled the World Health Organization criteria for OP. One year later, the patients were asked to return for a followup DXA. Admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…In a meta-analysis of six studies pooling over 171,000 patients, non-compliant patients had a 46% greater risk of experiencing fracture than their compliant counterparts, with the risk of vertebral fracture higher than hip or non-vertebral fracture [ 10 ]. Poor compliance has also been shown to affect BMD: among a population of nearly 250 women in a managed care plan, those receiving bisphosphonates or estrogen with MPR ≥66% had greater increases in BMD than those with MPR <66% [ 28 ]. Because the clinical benefit of osteoporosis therapies diminishes over time upon discontinuation, persistence and compliance with medications is critical in minimizing the risk of bone fractures [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of six studies pooling over 171,000 patients, non-compliant patients had a 46% greater risk of experiencing fracture than their compliant counterparts, with the risk of vertebral fracture higher than hip or non-vertebral fracture [ 10 ]. Poor compliance has also been shown to affect BMD: among a population of nearly 250 women in a managed care plan, those receiving bisphosphonates or estrogen with MPR ≥66% had greater increases in BMD than those with MPR <66% [ 28 ]. Because the clinical benefit of osteoporosis therapies diminishes over time upon discontinuation, persistence and compliance with medications is critical in minimizing the risk of bone fractures [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prior study suggested that more than half of patients (58%) resumed osteoporosis treatment during the 1 year after a BMD test [35]. Therefore, BMD testing has a temporal relationship with increased osteoporosis medication use over follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, baseline osteoporosis medication and BMD testing showed an increased likelihood for further osteoporosis treatments being prescribed. A prior study suggested that more than half of patients (58%) resumed osteoporosis treatment during the 1 year after a BMD test [ 35 ]. Therefore, BMD testing has a temporal relationship with increased osteoporosis medication use over follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In prospective studies, patients who underwent DXA subsequently had better adherence to their treatment regimen [23].…”
Section: Usefulness Of Dxa For Monitoring Osteoporosis Treatmentsmentioning
confidence: 99%